THE ROLE OF EDUCATION AND SCIENCE IN THE DIGITAL TRANSFORMATION OF SOCIETY - E. Butenko (Вестник Северо-Кавказского федерального университета)
The purpose of this article is to study the specifics of the development of modern education as an integral part of digitalization. The article presents a comparative analysis of the number of specialists in secondary and higher qualifications in ICT and the demand for master's and undergraduate programs and specialties, noted that there was a serious problem in scientific capacity and building human resources in the quality of the academic staff, if the trend continues in the future, we will incur huge losses in high-tech sectors, manufacturing and science in General. The role of mutual influence of education, science and the state is defined. According to the results of the study, it is concluded that the key driver influencing the development of the regulatory environment is the sphere of education and science, which requires state support and, in turn, the state creates a favorable environment by consuming a digital product. Analyzing the structure of the digital economy as a sphere of human activity to meet human demandfor various goods, including education, the author suggests considering the digital economy as one of the elements of the economy that are part of its infrastructure.